Effects of increased cognitive load on field of view in multi-task operations involving surveillance - Goh, Marcus Seng Yuen (2021)
Many multi-task operations require human operators to simultaneously perform visual surveillance and a secondary task. As the trend in the technological advancement of surveillance systems indicates high likelihood of heavy interdependence between human and technology in the foreseeable future, it is paramount to venture beyond the context of driving, an area where similar research is saturated in, and investigate the functional field of view (FFoV) of multi-tasking human operators in other operations involving surveillance. In the present study, we investigated the effects of multi-tasking and stimulus parameters (size and contrast) on the response accuracy and response time for identifying visual targets appearing within one’s visual field. Mixed analyses of variance revealed that only response time was negatively affected by multi-tasking, while both response accuracy and response time deteriorated as either the size or contrast of the visual targets decreased. In addition, a significant interaction effect between the investigated parameters of the visual target on response accuracy implies the need for multi-task operations involving surveillance to consider such and future findings critically as they evolve their technology and systems to aid the human operators. The current findings provide insights for surveillance and air traffic control (ATC) operations in future studies.